Coronavirus disease 2019: laboratory diagnosis - Rodríguez Sáenz, Ana Yervid; Camacho Valero, Janneth Marcela (Subcomité editorial y de evaluación de obras de la Facultad de Ciencias de la Salud Editora Revista Dra. Bibiana Matilde Bernal Gómez, 2020)
Coronavirus disease 2019, (Coronavirus Disease 2019, COVID-19), is caused by the Severe Acute Respiratory Syndrome Coronavirus or Severe 2 (SARS-CoV-2). For its diagnosis there are three types of tests: those based on the detection of the virus (RNA or viral antigen), on the detection of antigens and those that detect antibodies. The Real- time Reverse Transcription Polymerase Chain Reaction (rRT-PCR) detects the genetic material (RNA) of the virus, it is the reference standard for diagnostic of COVID-19; tests that detect antigens (virus proteins) may be useful as a criterion to confirm that the virus is present at the time the sample is taken and test that detect antibodies (IgM/IgG) indicate that there has been previous contact with the virus. Laboratory tests are used as help diagnostic and show findings that may lead to suspicion of COVID-19.